Catastrophic stress corrosion failure of Zr-base bulk metallic glass through hydrogen embrittlement. (October 2019) - Geissler, D.; Uhlemann, M.; Gebert, A.
Highlights: An in-depth review on corrosion, stress corrosion and hydrogen uptake is provided. Stress corrosion cracking (SCC) experiments with in situ pH value measurement. pH value drop during SCC proves proton formation during initial pitting corrosion. Solvation characteristics of the Zr 4+ cation are responsible. Solvation characteristics of the Zr4+ cation are responsible. Abstract: Zr-base bulk metallic glasses (BMG) are prone to pitting corrosion in halide containing solutions and also stress corrosion cracking (SCC) is often interpreted in this context. This work presents in situ SCC experiments on notched Zr52.5 Cu17.9 Ni14.6 Al10 Ti5 (at.%) BMG bars under 3-point bending in dilute NaCl solution. They show that pitting corrosion is only the initiating process. The pitted areas have a lower local corrosion potential and the reaction of Zr 4+ to zirconyl ions in solution produces H + that can be reduced and absorbed in the local acidic environment. So, hydrogen embrittlement causes the observed catastrophic failure and peculiar fracture surface characteristics.